2017
DOI: 10.1063/1.4979720
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous sound attenuation in Voronoi liquid

Abstract: The physics of simple fluids in the hydrodynamic limit and notably the connection between the proper microscopic scales and the macroscopic hydrodynamical description are nowadays well understood. In particular, the three peak shape of the dynamical structure factor S(k,ω) is a universal feature, as well as the k-dependence of the peak position (∝k) and width ∝k, the latter accounting for the sound attenuation rate. In this paper, we present a theoretical model of monodisperse fluid, whose interactions are def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…This decomposition of the total force F i as a sum of pair terms F j→i verifies the properties expected from such a decomposition : one has F j→i parallel to r ij and F j→i = −F i→j by a simple verification (the term proportional to R 2 − R 2 i , absent in the monodisperse system [5], is required here to ensure the latter antisymmetry). In other words, this pair force decomposition complies with the so-called strong third Newton law (the law of action-reaction with F j→i parallel to r ij ).…”
Section: E Stress Tensorsupporting
confidence: 70%
See 3 more Smart Citations
“…This decomposition of the total force F i as a sum of pair terms F j→i verifies the properties expected from such a decomposition : one has F j→i parallel to r ij and F j→i = −F i→j by a simple verification (the term proportional to R 2 − R 2 i , absent in the monodisperse system [5], is required here to ensure the latter antisymmetry). In other words, this pair force decomposition complies with the so-called strong third Newton law (the law of action-reaction with F j→i parallel to r ij ).…”
Section: E Stress Tensorsupporting
confidence: 70%
“…In future work, we will study the dynamics of this model, with a particular emphasis on the glass transition scenario. We have shown in [5] that the dynamical properties of the Voronoi liquid could be quite different from that of ordinary liquids. It is interesting to see to what extent deviations with respect to the "usual" behaviour could also show up in the binary Voronoi liquid.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They found that a glass-like regime with caging behavior and subdiffusive dynamics can be achieved if the rate of cell cycling is sufficiently low. Finally, a recent series of papers by Ruscher and co-workers [143][144][145] studied the glassy physics of the so-called Voronoi liquid, which is defined such that each Voronoi position tends to move towards the centroid of the Voronoi cell to which it belongs. Although this model was not motivated by biological experiments, it revealed a multitude of non-trivial glassy features; it will be interesting to explore if and how the Voronoi liquid can be linked to other Voronoi-based models of confluent living cells.…”
Section: Vertex and Voronoi Modelsmentioning
confidence: 99%